Preoperative Computerized Tomography and Magnetic Resonance Imaging of the Pancreas Predicts Pancreatic Mass and Functional Outcomes After Total Pancreatectomy and Islet Autotransplant. Issue 7 (August 2016) - Young, Michael C.; Theis, Jake R.; Hodges, James S.; Dunn, Ty B.; Pruett, Timothy L.; Chinnakotla, Srinath; Walker, Sidney P.; Freeman, Martin L.; Trikudanathan, Guru; Arain, Mustafa; Robertson, Paul R.; Wilhelm, Joshua J.; et al.
Abstract : Objectives: Approximately two thirds of patients will remain on insulin therapy after total pancreatectomy with islet autotransplant (TPIAT) for chronic pancreatitis. We investigated the relationship between measured pancreas volume on computerized tomography or magnetic resonance imaging and features of chronic pancreatitis on imaging, with subsequent islet isolation and diabetes outcomes. Methods: Computerized tomography or magnetic resonance imaging was reviewed for pancreas volume (Vitrea software) and presence or absence of calcifications, atrophy, and dilated pancreatic duct in 97 patients undergoing TPIAT. Relationship between these features and (1) islet mass isolated and (2) diabetes status at 1-year post-TPIAT were evaluated. Results: Pancreas volume correlated with islet mass measured as total islet equivalents ( r = 0.50, P < 0.0001). Mean islet equivalents were reduced by more than half if any one of calcifications, atrophy, or ductal dilatation were observed. Pancreatic calcifications increased the odds of insulin dependence 4.0 fold (1.1, 15). Collectively, the pancreas volume and 3 imaging features strongly associated with 1-year insulin use ( P = 0.07), islet graft failure ( P = 0.003), hemoglobin A1c ( P = 0.0004), fasting glucose ( P = 0.027), and fasting C-peptide level ( P = 0.008). Conclusions: Measures of pancreatic parenchymal destruction on imaging, including smaller pancreas volume and calcifications, associate strongly with impaired islet mass and 1-year diabetes outcomes. Abstract : Supplemental digital content is available in the text.